2004
DOI: 10.1152/physiolgenomics.00109.2004
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia-enhanced splenic cytokine gene expression is mediated by the sympathetic nervous system

Abstract: . Hyperthermia-enhanced splenic cytokine gene expression is mediated by the sympathetic nervous system. Physiol Genomics 19: 175-183, 2004. First published August 3, 2004 doi:10.1152/physiolgenomics.00109.2004.-Whole body hyperthermia (WBH) has been used in experimental settings as an adjunct to radiochemotherapy for the treatment of various malignant diseases. The therapeutic effect of WBH has been hypothesized to involve activation of the immune system, although the effect of hyperthermia-induced activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 57 publications
1
29
0
Order By: Relevance
“…In recent studies, we found that whole body hyperthermia and central ANG II infusion increased both the level of splenic sympathetic nerve activity and the expression of selective splenic cytokine and chemokine genes (19,20). The enhanced splenic gene expression to these interventions was abrogated by denervation of splenic sympathetic nerves, suggesting a role for splenic sympathoexcitation in upregulation of selective splenic cytokine genes.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…In recent studies, we found that whole body hyperthermia and central ANG II infusion increased both the level of splenic sympathetic nerve activity and the expression of selective splenic cytokine and chemokine genes (19,20). The enhanced splenic gene expression to these interventions was abrogated by denervation of splenic sympathetic nerves, suggesting a role for splenic sympathoexcitation in upregulation of selective splenic cytokine genes.…”
Section: Discussionmentioning
confidence: 84%
“…For monitoring during the experiment and for subsequent data analysis, the filtered neurograms were routed to an oscilloscope and a nerve traffic analyzer. Sympathetic nerve potentials were full-wave rectified, integrated (time constant 10 ms) and quantified as volts ϫ seconds (V ⅐ s) (19,20,28,29). SND was corrected for background noise after administration of the ganglionic blocker, trimethaphan camsylate (10 -15 mg/kg iv).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations